Challenges of a Long-Lived Society as an Opportunity for Restructuring Organizations - Mežnar, Dušan (45th International Conference on Organizational Science Development: Organization and the Longevity Society, Conference Proceedings, 2026)
Demographic change and population ageing are among the key structural forces shaping the future of organizations. Longer working lives, the coexistence of multiple generations in the workplace, and rapid digital transformation create complex challenges while also offering significant development opportunities. Modern organizations simultaneously employ members of Generations X, Y, and Z, who differ in work values, competencies, attitudes toward technology, and leadership expectations. This article examines the long-lived and multigenerational workforce as a strategic opportunity for organizational restructuring at the strategic, process, and human resources levels. Based on a review of contemporary literature on age diversity, knowledge management, ergonomics, and digitalization, a descriptive conceptual model of organizational renewal is proposed. The model includes multigenerational diagnosis, generation-sensitive strategic planning, process and organizational redesign, competency and human resource adaptation, and the development of an inclusive organizational culture and communication. The findings suggest that organizations which view demographic challenges as a source of development potential achieve greater resilience, innovation capacity, and long-term sustainability.